Penerapan Algoritma C4.5 Dalam Penilaian Kepuasan Pelanggan Terhadap Layanan (Studi Kasus: Nilla Wedding Gallery) - Riska Sulistiani; Diana Yusuf; Vany Terisia (ITB Ahmad Dahlan Jakarta, 2023)
Nilla Wedding Gallery is a service provider engaged in cosmetology and wedding management. During the run, existing customer data has never been managed optimally only limited to piles of data and has never used the data mining process to find patterns or information from service sales data to customers. Data Mining is a technique that processes or manages data into information. In this study the author uses the C4.5 algorithm method, the C4.5 method is used as an approach to generate a prediction model based on attributes relevant to customer satisfaction. Data obtained from a case study at Nilla Wedding Gallery was used to train and test the C4.5 model. As a form of this effectiveness, the author built a web mining system using the PHP programming language. The results showed that the C4.5 algorithm is effective in identifying factors that affect customer satisfaction, and is able to produce decisions that are beneficial for policy making by Nilla Wedding Gallery in improving service quality and achieving higher customer satisfaction.